Inovasi Berkelanjutan dalam Bisnis: Manfaatkan Flowchart untuk Mengoptimalkan Nilai Limbah Perusahaan - Kus Indrani Listyoningrum; Danise Yunaini Fenida; Nurhasan Hamidi (Jurnal Informasi Pengabdian Masyarakat, 2023)
Indonesia as a large industrial country contributes 20% of GDP. However, the lack of awareness of waste during production creates problems. Inorganic waste, such as plastic pipes, is often disposed of at a low value. An effective strategy is to use flowcharts. Flowcharts help understand complex steps, team communication, and identify waste reduction opportunities. At PT Nova Indonesia, flow diagrams are used to develop new products from pipe waste. This simplifies processes, reduces errors, and creates high-value products from waste. With the development of the right flow chart, waste can be reprocessed into quality products, supporting the environment and industrial sustainability.